Energy balance and evapotranspiration of melon grown with plastic mulch in the Brazilian semiarid region (Scientia Agricola, 2015)
Melon plants (Cucumis melo L.) are grown in the state of Rio Grande do Norte (RN), the largest producer of melons in Brazil, with plastic mulch and agrotextiles. Studies of crop evapotranspiration (ET) under these conditions are required to ensure adequate irrigation. This study aimed to determine the crop coefficients (Kc) of irrigated melon plants grown with mulch and agrotextiles in the region of Mossoró, RN, based on the Bowen Ratio Energy Balance (BREB) method. Two experiments were conducted at different times during the 2009/2010 season in a melon producing area (4°59'52" S, 37°23'09" W, and 54 m elevation) to define ET and Kc. Due to the plastic cover and reduced precipitation during the experiments, the Kc obtained by the BREB method was considered the basal Kc - KcbBREB. The results were compared with the Kcb from the FAO 56 Bulletin. There was close agreement between BREB and FAO ET measurements (12 % underestimation by the FAO method for the entire crop season), with sizeable differences only during the initial phenological stage. The mean KcbBREB values of the two field campaigns were 0.26, 0.96 and 0.63 for the initial, midseason and late stages, respectively. The high KcbBREB value in the initial growth phase may be related to the effect of the plastic mulch and agrotextiles on the energy balance at the surface. The relationship between KcbBREB and fc had high correlation, making possible an estimation of the melon Kcb based on the level of crop ground cover.